Parabolic revolution surfaces of finite type in simply isotropic 3-spaces - Akbay, Alev Kelleci (World Scientific Publ Co Pte Ltd, 2021)
In this paper, we classify parabolic revolution surfaces in the three-dimensional simply isotropic space II3 under the condition Delta(J)x(i) = lambda(i)x(i), J = I, II, where Delta(J) is the Laplace operator with respect to first and second fundamental form and lambda(i), i = 1, 2, 3 are some real numbers. Also, as an application, we give some explicit examples for these surfaces.
Keywords: Simply isotropic space; parabolic revolution surfaces; invariant surface; Laplace operator; surfaces of finite type; Cayley-Klein geometry